2015
DOI: 10.1016/j.jplph.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of individual and combined effects of salinity and deficit irrigation on physiological, nutritional and ornamental aspects of tolerance in Callistemon laevis plants

Abstract: SummaryThe effect of water deficit, salinity and both applied simultaneously on several physiological and morphological parameters in the ornamental plant Callistemon laevis was studied to identify the tolerance mechanisms developed by this species to these sources of stress and to evaluate their adaptability to such conditions. C. laevis plants were grown in pots outdoors and subjected to four irrigation treatments lasting ten months: control (0.8 dS m -1 , 100% water holding capacity), water deficit (0.8 dS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 69 publications
3
23
1
1
Order By: Relevance
“…Also, these changes, induced by salinity, have the potential to improve crop quality by reducing excessive vigour and promoting a more compact habit [49]. However, the level of soil salinity is important, and irrigation with high salt concentrations provokes a decrease in this ratio (leaf area/plant height) due to a reduction in both components which could negatively affect the commercial quality of plants [93,95].…”
Section: Visual and Aesthetic Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, these changes, induced by salinity, have the potential to improve crop quality by reducing excessive vigour and promoting a more compact habit [49]. However, the level of soil salinity is important, and irrigation with high salt concentrations provokes a decrease in this ratio (leaf area/plant height) due to a reduction in both components which could negatively affect the commercial quality of plants [93,95].…”
Section: Visual and Aesthetic Qualitymentioning
confidence: 99%
“…Depending on the ability of plants to grow in saline environments, they are classified as either glycophytes or euhalophytes, and their response to salt stress differs in terms of toxic ion uptake, ion compartmentation and/or exclusion, osmotic regulation, CO 2 assimilation, photosynthetic electron transport, chlorophyll content and fluorescence, reactive oxygen species (ROS) generation, and antioxidant defences [11][12][13][14]. Most salinity adaptive mechanisms in plants are Callistemon citrinus 4 dS·m −1 NaCl 56 days Leaf DW, stem DW, stem diameter, root DW, total DW, root:shoot DW ratio, total leaf area, plant height, root morphology parameters, RGR [42] Lawsonia inermis L. 75, 150 mM NaCl 53 days Total FW, shoot:root DW ratio, RGR [94] Myrtus communis L. 4, 8, 12 dS·m −1 NaCl 30 days Leaf DW, stem DW, root DW, root:shoot DW ratio [28] Eugenia myrtifolia 4, 8, 12 dS·m −1 NaCl 30 days Leaf FW, leaf DW, total leaf area, leaf water content, stem DW, root DW, root:shoot DW ratio [29] Callistemon laevis 4 dS·m −1 NaCl 300 days Leaf DW, leaf area, stem DW, root DW, plant height, root:shoot DW ratio, plant compactness (leaf area/ height) [95] Myrtus communis L. 2.0, 5 dS·m −1 10.0 dS·m −1 RW NaCl 90 days Leaf DW, stem DW, root DW, total DW, root:shoot DW ratio [6] Viburnum lucidum Callistemon citrinus 200 mM NaCl 103 days Leaf number, leaf area, shoot DW, apical shoot length, lateral shoot length, lateral shoots, plant height, root DW, root:shoot DW ratio [8] Verbana bonariensis L. 200 mM NaCl 2013-2014 Total plant height, FW of aboveground part, visual score [96] Gómez-Bellot et al [45] reported increases in the root to shoot ratio in E. japonica plants irrigated with an NaCl solution with an electric conductivity (EC) of 4 dS m −1 . The use of saline water in C. citrinus plants also slightly decreased aerial growth, increased the root to shoot ratio and improved the root system (increase in root diameter and root density) [42].…”
Section: Introductionmentioning
confidence: 99%
“…Also, these changes, induced by salinity, have the potential to improve crop quality by reducing excessive vigour and promoting a more compact habit [49]. However, the level of soil salinity is important, and irrigation with high salt concentrations provokes a decrease in this ratio (leaf area/plant height) due to a reduction in both components which could negatively affect the commercial quality of plants [76,77].…”
Section: Visual and Aesthetic Qualitymentioning
confidence: 99%
“…The effect of drought stress on plant growth and dry matter has been noticed in numerous ornamental species-for example, Pistacia [12], Spiraea, Pittosporum [19], Bougainvillea [20], Callistemon [21], Laurus, and Thunbergia [22] (Table 1). Since the photosynthetic pathways strongly influence the response to water stress, only the responses of C3 plants are presented in Table 1.…”
Section: Growth and Morpho-anatomical Modificationmentioning
confidence: 99%
“…2-year-old rooted cuttings Total biomass (−); plant height (−); osmotic adjustment (−), leaf tissue elasticity (−) [21] Viburnum opulus L. and Photinia x fraseri 'Red Robin' bushy shrubs…”
Section: Callistemon Laevis Bushy Shrubmentioning
confidence: 99%